2020
DOI: 10.1088/1748-0221/15/10/c10029
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in digital Positron Emission Tomography

Abstract: A: Positron Emission Tomography (PET) is a non-disruptive functional imaging technique, which provides a high resolution and high-sensitivity measurement of the functional processes in biological systems. The recent developments in biology and radio-chemistry enabled PET to study an increasing number of functional processes, but became highly demanding in terms of sensitivity, spatial resolution, and adaptability to the variable size of the biological systems ranging from few millimeters up to several centimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Finally, the brain of the mouse was segmented with a threshold-based algorithm by using the standardized uptake value (SUV) of the PET image, followed by a topological closure. The segmented brain images were co-registered with a mouse brain atlas (Ma et al, 2005;D'Ascenzo et al, 2020) by using a mutual information method, and 19 brain regions were identified, as reported in Table 1. Finally, the SUV of each mouse was calculated both in the entire brain and in each of the segmented brain regions separately.…”
Section: Chronic Sleep Fragmentation Modelingmentioning
confidence: 99%
“…Finally, the brain of the mouse was segmented with a threshold-based algorithm by using the standardized uptake value (SUV) of the PET image, followed by a topological closure. The segmented brain images were co-registered with a mouse brain atlas (Ma et al, 2005;D'Ascenzo et al, 2020) by using a mutual information method, and 19 brain regions were identified, as reported in Table 1. Finally, the SUV of each mouse was calculated both in the entire brain and in each of the segmented brain regions separately.…”
Section: Chronic Sleep Fragmentation Modelingmentioning
confidence: 99%